Investigating sex offending representation among politicians through Twitter - Veggi, Sara (The journal of forensic psychiatry & psychology, 2023)
Sex violence is a sensitive topic that provokes public debate, due in part to the influential role of the media in taking crime cases out of the courts to the general public. This has led to a punitive attitude toward sex-offenders that has fostered the view of ‘once a sex-offender, always a sex-offender’. Using a linguistic analysis of Tweets, we examined how sex-offending and sex-offenders are portrayed by 782 Italian politicians. Results show that politicians shared fewer positive posts about sex-offending than the average of posts found on Twitter, with an emotional negative overtone dominating the sex-offending narrative rather than eliciting a cognitive response. Among emotions, anger was most prevalent, followed by sadness and anxiety. In addition, politicians’ portrayals of sex-offenders were consistently negative regardless of their political orientation. Social communication is critical in conveying unbiased information and fostering fruitful discussion about how to deal with sex-offenders, especially because politicians are responsible for making decisions and influencing legislation on such a controversial topic. A less emotionally driven response could promote a more evidence-based approach to managing sex-offenders prior to their release into the community, thereby increasing the likelihood of desistance from crime.